ANALISIS PEMAHAMAN MATEMATIS SISWA DITINJAU DARI MOTIVASI BELAJAR PADA PEMBELAJARAN TATAP MUKA (PTM) TERBATAS - Desi Dwi Amelia; Dwi Ivayana Sari; Nur Aini S (SIGMA, 2022)
This study aims to analyze students' mathematical understanding in terms of learning motivation in limited face-to-face learning. This type of research is qualitative research. Subjects were taken using a learning motivation questionnaire and a mathematical ability test. Students who meet the indicators of learning motivation and the characteristics of the category of mathematical ability are determined as subjects and then given a mathematical understanding test and then interviewed. The data were then analyzed using the Miles and Huberman model. The results of data analysis show that students who have high learning motivation meet three indicators of mathematical understanding, namely the ability to classify objects according to certain properties (according to the concept), the ability to present concepts in various forms of mathematical representation and the ability to use, utilize and choose procedures or certain operations. However, students have problems in using and utilizing certain perating procedures. Subjects with moderate learning motivation only met two indicators of mathematical understanding, namely the ability to classify objects according to certain properties (according to the concept) and the ability to use, utilize and choose certain procedures or operations. However, students who are motivated to learn are having problems using and utilizing certain operating procedures. Subjects with low learning motivation fulfill one indicator of mathematical understanding, namely the ability to classify objects according to certain characteristics (according to the concept). Even though students do not work on the questions correctly, students still try to solve the questions given. It is recommended that teachers pay attention to students' mathematical understanding, especially in the new normal period.